Thermodynamic Explanation for the Large Difference in Improving Shape Memory Effect of Fe–Mn Alloys by Co and Si Addition1 . Issue 8 (3rd May 2016) - Chen, Jie; Sun, Jiangwei; Yang, Qin; Peng, Huabei; Wang, Shanling; Wen, Yuhua
Abstract : The authors investigate the shape memory effect (SME) and microstructure evolution of the Fe–25Mn, Fe–25Mn–6Co, and Fe–25Mn–6Si alloys before and after deformation at room temperature (RT) through ex situ optical observation. After deformation, the stress‐induced reverse transformation of thermal ϵ martensite, an unrecovered deformation mode, can be easily observed in the Fe–25Mn and Fe–25Mn–6Co alloys, but it can be hardly observed in the Fe–25Mn–6Si alloy. The lower values of chemical driving force for ϵ → γ transformation at RT lead to the occurrence of the stress‐induced reverse transformation of thermal ϵ martensite and the poorer SME in the Fe–Mn and Fe–Mn–Co alloys than in the Fe–Mn–Si alloy. Abstract : This figure shows that the values of chemical driving force for ϵ → γ transformation ( Δ G c h ϵ → γ ) at room temperature (RT) in the Fe–Mn and Fe–Mn–Co alloys are much lower than in Fe–Mn–Si alloy. This result leads to the occurrence of the stress‐induced reverse transformation of thermal ϵ martensite and the poorer shape memory effect in the Fe–Mn and Fe–Mn–Co alloys than in the Fe–Mn–Si alloy.